4y - x = 5 + 2y ..... (1)
3x + 7y = 24 ..... (2)
by grouping like terms in (1)
4y - x = 5 + 2y
4y - 2y - x = 5
<span>-x + 2y = 5 </span> ..... (1a)
by multiplying (1a) through by -3
(-3)(-x) + 2(-3)y = 5(-3)
3x - 6y = -15 ..... (1b)
by subtracting 1a from 2
3x -3x + 7y - (-6y) = 24 - (-15)
13y = 39
⇒ y = 3
by substituting y=3 into (2)
3x + 7(3) = 24
3x = 24 - 21
3x = 3
⇒ x = 1
∴ solution to the system is x=1 when y = 3
Answer:
3x + 2y = 17
2x + 5 y = 26
Step-by-step explanation:
3x + 2y = 17 }
2x + 5 y = 26}
x - 3y = - 9
x = -9 + 3y
=> 2 (-9+3y)+5y=26
-18+6y+5y=26
-18+11y=26
11y=26+18
11y=44
y= 4
3x + 8=17
3x = 17 - 8
3x = 9
x = 9 : 3
x = 3
Answer:
The correct answer is a.
Step-by-step explanation:
The domain is the plotted points on the x-axis.
The range is the plotted points on the y-axis.
(-3, 3), (0, 0), (2, -2)
Domain {-3, 0, 2}; Range: {3, 0, -2}
Domain: {-5, 7}
Range: {-9, 4, 8}